Grundlegende betrachtungen zur wirkung eines "inversen" spanungsverhältnisses als basis für die fräswerk-zeugkonstruktion - Jakubov, Tschingiz; Duc, Tran Minh; Nguyen, Trong Hieu; Schmidt, Konrad; Emmer, Emmer (НТУ "ХПІ", 2012)
The demand for higher productivity and quality, flexibility as well as process safety are marking the development in the field of metal-cutting manufacturing process. Thereby the field of low vibration milling plays a special role. Therefore the development and design of modern milling tools is more and more often affected by novel machining strategies. The article deals with the development and design of a low vibration milling tool including the reversal of conventional chip- cross- section b/h > 1 to the "invers" ratio b/h < 1. For this the difference between the two cross sections will be analysed. The focus of the first experimental research is the determination of the effects of reversing the chip- cross- section on the cutting forces as well as chip formation and - forming. The influence of the tool side rake angle (γf) in milling with "inverse" chip- cross- section will be studied. The results gathered in the field of "inverse" chip- cross- ratio provides the base for formulation of design fundamentals and drafts of a novel milling tool with peeling function.